PENGARUH KETERSEDIAAN SARANA PERPUSTAKAAN DAN STRATEGI MENGAJAR GURU TERHADAP PENGUATAN LITERASI MEMBACA SISWA SMP: STUDI PADA SMP NEGERI 1 BATUDAA - Aprianita Saputri Polohi; Radia Hafid; Mamang Kasim; Melizubaida Mahmud; Cristian Polamolo (Pascasarjana Universitas Pendidikan Ganesha, 2026)
This study aims to determine the effect of library facilities availability and teachers' teaching strategies on strengthening students' reading literacy at SMP Negeri 1 Batudaa. Reading literacy is a fundamental skill that plays an important role in supporting students' academic success; however, some students still experience difficulties in reading and comprehending texts. This study employed a quantitative approach with a correlational survey design. The population consisted of all seventh-grade students at SMP Negeri 1 Batudaa, totaling 115 students, while 53 students were selected as the sample using purposive sampling. Data were collected through observation, documentation, and questionnaires using a Likert scale. The data were analyzed using validity, reliability, and normality tests, as well as multiple linear regression, t-tests, F-tests, and the coefficient of determination test. The results revealed that the availability of library facilities had a positive and significant effect on students' reading literacy (β = 0.348; p = 0.046), while teachers' teaching strategies showed a stronger positive and significant effect (β = 0.414; p = 0.010). Simultaneously, both variables had a positive and significant effect on reading literacy and explained 50.7% of the variance in students' reading literacy (R² = 0.507), while the remaining variance was influenced by other factors outside the model. These findings indicate that improving library facilities and teachers' teaching strategies can effectively strengthen students' reading literacy.